Incidence and outcome of Acute Kidney Injury in patients admitted in a level III ICU in Nepal: A retrospective, observational study - Adhikari, Suraj; Koirala, Sabin; Pandey, Shama; Karki, Arjun (Journal of Nepalese Society of Critical Care Medicine, 2024)
Background and aims: Acute kidney injury (AKI) is associated with increased mortality, morbidity, and hospital stay. AKI is seen in 20-60% of patients admitted to the intensive care unit (ICU), and mortality is as high as 50% if not managed timely. Burden of AKI is more in developing countries as compared to the developed ones. There is a paucity of published literature regarding incidence and outcome of AKI in critically ill patients from lower-middle income countries like Nepal. This study aimed to determine the incidence and outcome of AKI in patients admitted to a level III ICU in Nepal. Methods: This observational study was conducted in the ICU of Hospital for Advanced Medicine and Surgery (HAMS) Hospital, Kathmandu, Nepal. Data over a period of one year was curated from ICU registry. Eligible patients were screened and the incidence of AKI in ICU admitted patients along with their outcomes (length of ICU stay, need of RRT and ICU mortality) were observed. Results: Among 881 patients admitted to the ICU, 660 patients were enrolled for analysis. Of them, 14.2% of patients developed AKI during ICU stay, out of which 5.3% received RRT and 19.1% died. The median (IQR) length of ICU stay for those who developed AKI was 4 (3-7) days. The 34.0% patients who developed AKI had sepsis. Conclusion: Patients admitted to ICU in this study have high incidence of AKI. In patients who developed AKI, sepsis was the leading cause of ICU admission.